2020
DOI: 10.1016/j.jdiacomp.2020.107637
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and diabetes: The why, the what and the how

Abstract: Background: The novel coronavirus SARS-CoV-2 has taken the world by storm. Alongside COVID-19, diabetes is a long-standing global epidemic. The diabetes population has been reported to suffer adverse outcomes if infected by COVID-19. The aim was to summarise information and resources available on diabetes and COVID-19, highlighting special measures that individuals with diabetes need to follow. Methods: A search using keywords "COVID-19" and "Diabetes" was performed using different sources, including PubMed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
145
1
27

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(177 citation statements)
references
References 54 publications
4
145
1
27
Order By: Relevance
“…N of donors 67 9 Gender (male/female) 37/30 5/4 Age (years) 59 ± 10 60.7 ± 12 Purity % 70 ± 17 60.1 ± 20 BMI (kg/m 2 ) 25.9 ± 3.5 28.1 ± 4.5 HbA1c…”
Section: Non-diabetics Diabeticsmentioning
confidence: 99%
“…N of donors 67 9 Gender (male/female) 37/30 5/4 Age (years) 59 ± 10 60.7 ± 12 Purity % 70 ± 17 60.1 ± 20 BMI (kg/m 2 ) 25.9 ± 3.5 28.1 ± 4.5 HbA1c…”
Section: Non-diabetics Diabeticsmentioning
confidence: 99%
“…Studies investigating the prevalence of diabetes (all types) in COVID-19 patients have found it to be around 10% [4,5], but it remains unclear whether people with diabetes are more susceptible to COVID-19 [6,7]. However, numerous studies have shown an increased risk of severe COVID- 19 and mortality in individuals with diabetes [4,[6][7][8][9][10][11][12], as well as higher rates of hospitalization due to COVID-19 [13,14]. Thus, individuals with diabetes have been identified as having worse COVID-19 outcomes, particularly those with poor glycemic control [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…These projections were computed before the onset of COVID-19 pandemic. The current global pandemic has had great implications on global mental health as well as on the management and care treatment of diabetes [39,40]. Hence, it is expected that both diabetes and depression will have a far higher global burden impact than previously projected.…”
Section: Discussionmentioning
confidence: 99%